The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1073/pnas.0915022107
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-based mechanism for the commitment of multipotent progenitors to a single cellular fate

Abstract: When stem cells and multipotent progenitors differentiate, they undergo fate restriction, enabling a single fate and blocking differentiation along alternative routes. We herein present a mechanism whereby such unequivocal commitment is achieved, based on micro-RNA (miRNA)-dependent repression of an alternative cell fate. We show that the commitment of monocyte RAW264.7 progenitors to active macrophage differentiation involves rapid up-regulation of miR-155 expression, which leads to the suppression of the alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 42 publications
6
91
3
1
Order By: Relevance
“…In addition, Mann et al performed a differential miRNA screening using the RAW 264.7 cell line under RANKL and M-CSF treatment to induce osteoclastic differentiation. miR-155 was described in this study as an early inhibitor of MITF, a nuclear effector that integrates M-CSF/RANKL signals to initiate the expression of osteoclast-specific genes (Mann et al 2010). The RAW 264.7 cell line can differentiate into either macrophages or osteoclasts, and the results of this study suggest that the upregulation of miR-155 expression facilitates macrophage commitment, therefore inhibiting osteoclast differentiation (by targeting MITF).…”
Section: Mirnas and Osteoclast Differentiationmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, Mann et al performed a differential miRNA screening using the RAW 264.7 cell line under RANKL and M-CSF treatment to induce osteoclastic differentiation. miR-155 was described in this study as an early inhibitor of MITF, a nuclear effector that integrates M-CSF/RANKL signals to initiate the expression of osteoclast-specific genes (Mann et al 2010). The RAW 264.7 cell line can differentiate into either macrophages or osteoclasts, and the results of this study suggest that the upregulation of miR-155 expression facilitates macrophage commitment, therefore inhibiting osteoclast differentiation (by targeting MITF).…”
Section: Mirnas and Osteoclast Differentiationmentioning
confidence: 65%
“…The RAW 264.7 cell line can differentiate into either macrophages or osteoclasts, and the results of this study suggest that the upregulation of miR-155 expression facilitates macrophage commitment, therefore inhibiting osteoclast differentiation (by targeting MITF). These data indicate that miR-155 is involved in the commitment switch of hematopoietic precursors (Mann et al 2010). Zhang et al (2012b) revealed that miR-155 is inhibited by IFNb during osteoclast differentiation, and they identified the effect of miR-155 on the 3 0 -UTR of MITF and suppressor of cytokine signaling 1 (SOCS1).…”
Section: Mirnas and Osteoclast Differentiationmentioning
confidence: 90%
“…9 Conversely, RANK targeting by miR-503 inhibited osteoclastogenesis, whereas silencing miR-503 enhanced in vivo bone resorption. 26 MiR-125a was also shown to inhibit osteoclast differentiation by suppressing TRAF6 expression, 27 whereas miR-155 was shown to regulate cell-fate commitment 28,29 It is important to recognize that the regulation of bone homeostasis depends on carefully orchestrated cross-talk between bone marrow cells. MiR-34c is an essential regulator of Notch signaling in osteoblasts, directly targeting Notch1, Notch2 and Jagged1, as well as Satb2 and Runx2.…”
Section: A Central Role For Mirnas In Bone Homeostasismentioning
confidence: 99%
“…These small, noncoding RNAs modulate gene expression at the post-transcriptional level and are responsible for regulating many biological processes including differentiation, 1 apoptosis, proliferation and cell-fate determination. 2 Considering the role miRNAs have in regulating these cellular processes, it is not surprising that dysregulation of miRNAs has been implicated in a variety of pathologies, such as inflammatory and autoimmune diseases, neurological disorders, 3 myocardial disease, 4 as well as several types of cancer.…”
Section: Introductionmentioning
confidence: 99%